Development of microsatellite markers in the Sparidae and their application in population genetics of the Hottentot seabream Pachymetopon blochii (Valenciennes, 1830) along the coast of South Africa - Bloomer, Paulette (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2011.